Expressing South African musical sensibilities In Jazz: the cultural relevance of John Coltrane and the musical impact of Mccoy Tyner - Dunjana, Thembelihle (College of Music, 2025)
This paper seeks to explore the cultural and spiritual relevance of John Coltrane (1926- 1967) and the musical impact of McCoy “Alfred” Tyner (1938-2020) on two contemporary South African pianists, with a focus on the music of Afrika Mkhize and Nduduzo Makhathini, as well as an insider's perspective of this subject in light of my own music, as a South African pianist. McCoy Tyner and John Coltrane are most famous for playing in the Coltrane classic quartet comprised of McCoy Tyner (piano), Jimmy Garrison/Steve Davis (bass), Elvin Jones (drums) and John Coltrane (saxophone) from the early to mid 1960s. The classic “Coltrane quartet sound” is tightly linked with the modal jazz sub-style and is marked by members' contributions such as Tyner's distinct minor, quartal and suspended harmonic voicings, Jones's extensive use of cross rhythms and dynamic intensity, Garrison's rhythmic drive and Coltrane's unique timbre on the tenor and soprano saxophone. Afrika Mkhize and Nduduzo Makhathini are contemporary local pianists who have contributed to current SA jazz repertoire. Several aspects of their music such as harmony, melodic phrasing, composition or underlying ideology display features reminiscent of Tyner and/or Coltrane. The primary point of departure is to explore possible reasons Tyner and Coltrane have impacted Mkhize and Makhathini (musically and otherwise). By paralleling the discourse of 1960s Black America (in which Coltrane's early works are situated) with cultural interests held by contemporary SA jazz artists, this paper evaluates how these discourses coincide, thereby answering the question: why are the musical aesthetics of Coltrane and Tyner relevant in echoing a South African jazz sensibility? The primary question is explored primarily through discussing the signiZicance of spirituality as well as understanding why Coltrane's integration of Indian and African musical elements make him a point of interest for contemporary South African musicians. The second question argues the signiZicance of McCoy Tyner's harmonic language in aiding a South African sensibility in jazz, through analysing the extent to which Tyner's minor- and quartal-based harmonies are apparent within these SA jazz pianists' compositional and improvisational style.